Rupture behavior and fracture mode for Inconel 625–9% Cr steel dissimilar welded joints at high temperature. (July 2021) - Wu, Guanzhi; Ding, Kai; Wei, Tao; Qiao, Shangfei; Liu, Xia; Gao, Yulai
Highlights: The creep rupture behavior under low stresses at high temperature is investigated. The brittle fracture is determined as the main failure mode. The relationship between the precipitates and eventual fracture is clarified. Graphical abstract: Abstract: In the present study, the rupture behavior and fracture mode for the Inconel 625–9% Cr steel dissimilar welded joints are investigated. The results reveal that the relationship between the rupture time and stresses follows the formula: lg ( t ) = − 0.028 σ + 6.75, while the microhardness measurement shows that the specimens with applied stresses under 620 ℃ both fracture in the heat affected zone of 9% Cr steel (9Cr-HAZ). Therefore, the microstructure of the 9Cr-HAZ adjacent to the fracture is emphatically observed, and it is found that the tempered martensite is the typical microstructure in 9Cr-HAZ. Simultaneously, massive micro-voids can be detected in 9Cr-HAZ along the grain boundaries. In addition, the particles around the micro-voids are identified as Laves phases combining with M23 C6 -type carbides. Thus by consuming the solid solution strengthening elements, especially W and Cr, the precipitation of these second phase particles softens the matrix, which can cause the formation of micro-voids. Subsequently, the initiation and convergence of those dispersed voids eventually lead to the failure of the ruptured specimens.